Soluble urokinase plasminogen activator receptor as a biomarker of antibiotic-resistant patterns of Gram-negative bacterial infections: a case-control study - Eliwi, Saif Hussain; Ali, May Mohammed; Al-Hasnawi, Sawsan (Pharmakeftiki, 2025)
The soluble urokinase plasminogen activator receptor (SuPAR) is an emerging biomarker associated with various clinical disorders; however, its utility in identifying antimicrobial-resistant (AMR) bacterial infections remains underexplored. AMR bacteria pose a significant global health challenge, with certain Gram-negative bacteria exhibiting considerable resistance to multiple antibiotics. This case-control study aimed at evaluating the diagnostic accuracy of SuPAR in detecting severe Gram-negative AMR bacterial infections. A total of 100 samples were analysed, comprising 60 clinically diagnosed cases of Gram-negative bacterial infections and 40 control samples. Pathogens were identified by using conventional laboratory techniques (including Gram staining, culture, colony morphology, and biochemical assays), supplemented by automated methods such as the VITEK2 Compact system for bacterial identification and antimicrobial susceptibility testing. Serum SuPAR levels were quantified via an enzyme-linked immunosorbent assay (ELISA). SuPAR levels were found to be significantly elevated in infected patients compared to controls (p=0.0006). Among the resistance profiles, extensively drug-resistant (XDR) infection cases exhibited the highest SuPAR levels, followed by multi-drug resistant (MDR) cases (p=0.0003). Non-MDR infection cases exhibited moderately elevated levels relative to controls. Across pathogen types, Acinetobacter baumannii was associated with the highest SuPAR levels, while Burkholderia cepacia exhibited the lowest. Notably, elevated SuPAR levels were also observed in cases of skin infection and sepsis. In conclusion, SuPAR levels were found to be markedly increased in patients with Gram-negative bacterial infections, particularly in those involving XDR and MDR strains, thereby suggesting its potential role as a biomarker in assessing antimicrobial resistance severity.